2018
DOI: 10.3390/ijerph15092010
|View full text |Cite
|
Sign up to set email alerts
|

“Sacbe”, a Comprehensive Intervention to Decrease Body Mass Index in Children with Adiposity: A Pilot Study

Abstract: Interventions in children with adiposity decrease less than 0.2 the body mass index (BMI) z-score less than 0.2 and only in 21–23% of cases. Experts recommend focusing on the habits of a healthy lifestyle (HLS) but considering the sociocultural context of children and their parents. Our objective was to achieve a higher percentage of success in lowering the BMI z-score in children with adiposity and their parents through a pilot program “Sacbe” based on HLS, sensitive to the sociocultural context previously ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Most of the studies showed decreased BMI z-scores of obese children and adolescents after 6 weeks to 6 months for each of the intervention studies. Theme-based nutritional sessions, involving portion size and food groups,51 feelings of hunger and satisfaction,52 nutrition counseling and phone calls,53 nutrition education group sessions and leaflets for caregivers,54 healthful and balanced diet with fruits and vegetables,55 and healthy beverage intake and increased consumption of fruits, nuts, legumes, vegetables, fish, and dairy products50 were implemented in childhood obesity intervention studies (data not shown).…”
Section: Recent Dietary Interventions and Outcomesmentioning
confidence: 99%
“…Most of the studies showed decreased BMI z-scores of obese children and adolescents after 6 weeks to 6 months for each of the intervention studies. Theme-based nutritional sessions, involving portion size and food groups,51 feelings of hunger and satisfaction,52 nutrition counseling and phone calls,53 nutrition education group sessions and leaflets for caregivers,54 healthful and balanced diet with fruits and vegetables,55 and healthy beverage intake and increased consumption of fruits, nuts, legumes, vegetables, fish, and dairy products50 were implemented in childhood obesity intervention studies (data not shown).…”
Section: Recent Dietary Interventions and Outcomesmentioning
confidence: 99%
“…All the studies targeted and included both males and female participants. Most of the studies (89.6%) were delivered in school settings, two (Martínez-Andrade et al, 2014;Rodriguez-Ventura et al, 2018) in public clinics, and one (Zacarías et al, 2019) in a community setting. One study (Martinez-Andrade et al, 2014) was delivered among a preschool population, 22 studies among a school-age population (6-12 years), and six among adolescents (13-18 years).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, significant improvements in dietary lifestyles were reported in these studies. Rodriguez-Ventura et al (2018) reported that the frequency of unhealthy dietary patterns decreased, but only some (e.g., eating more fruits and vegetables and breakfast consumption) were significant (p < 0.05). Elizondo-Montemayor et al…”
Section: Dietary Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors’ approach may serve as a model for further research efforts in health promotion in complex systems. Rodriguez-Ventura et al studied a pilot program focusing on healthy lifestyle which considered the socio-cultural context of the participants and their parents [22]. The program involved group sessions and active parent participation.…”
mentioning
confidence: 99%